Crack growth based life prediction approach under LCF-HCF interaction (Fracture and Structural Integrity, 2019)
Prediction of cyclic life under low cycle fatigue - high cycle fatigue (LCF-HCF) interaction is of paramount importance in the context of structural integrity of components in the primary side of fast reactors where such damage under LCF-HCF interaction occurs. The present investigation deals with the crack growth behavior of a type 316LN austenitic stainless steel subjected to simultaneous application of LCF and HCF cycles (block-loading). Tests were performed over a wide range of temperatures from ambient to 923 K. Experimental results indicate that a critical crack-length (acr) exists, beyond which the LCF-HCF interaction becomes significant. An attempt was made to predict life under block cycling by estimating the acr using fatigue crack threshold (ΔKth) since the latter is known to be affected significantly by the loading history. A universal equation, based on the concept of an equivalent critical crack length (acr.,eq) which incorporates the damage contribution from DSA and ratcheting under combined LCF-HCF loading, was proposed for life estimation.
Keywords: LCF; HCF; LCF-HCF interaction; Crack growth; 316LN SS